U-Pb dating of magmatic and xenocryst zircons from Mangakino ignimbrites and their correlation with detrital zircons from the Torlesse metasediments, Taupo Volcanic Zone, New Zealand - McCormack, K.; Gee, M.; McNaughton, Neal; Smith, Richard; Fletcher, Ian (Elsevier, 2009)
Mangakino ignimbrites are a sequence of voluminous eruptive units in the rhyolitic Mangakino Volcanic Centre (MVC) caldera complex, Taupo Volcanic Zone, New Zealand. U-Pb dating of 113 zircons extracted from four Mangakino ignimbrites revealsmagmatic and xenocrystic zircons. Magmatic zircon ages from three ignimbrites are slightly older than K/Ar and 40Ar/39Ar ages. Magmatic zircon age-spectra are tightly clustered and support a simple crystallisation history for these three ignimbrites. It is possible that the assimilation of zircon antecrysts leads to magmatic zircon spectra for the Ahuroa ignimbrite being >or=70 ka older than the 40Ar/39Ar age. Xenocrystic zircon age spectra correlate with spectra of detrital zircons from the underlying Mesozoic Torlesse metasediments. Our data are consistent with significant assimilation of metasediments and the incorporation of zircon prior to eruption. Systematic variations in the age spectra of xenocrystic zircons in successive Mangakinoignimbrites may be related to the structural development of the North Island, New Zealand.